Pengaruh Skarifikasi dan Media Tumbuh Terhadap Viabilitas Benih dan Vigor Kecambah Aren - Muhammad Salim Saleh; Enny Adelina; Endang Murniati; Tati Budiarti (Jurnal Ilmu Pertanian Indonesia, 2008)
The research aims to find out the effect of seed scarification and germination substrat to seed viability and seedling vigor of aren. The Experiment applied a group random design (RAK) with factorial style consiting of two factors. The first factor are scarification treatment:S0=without scarification, S1=scarification+trcatment 40 oC, S2=scarification+KN03 0.5%, soaked for 36 hours+tempcrature 40oC, the second factor arc germination substrat: M0=sand, M1=rice coal, M2=cocopith, M3=soil from palm tree+organic materil (1:1), M4=M3+fertilizer NPK (1 g per kg media). The highest seed germination was found in the scarification+KN03 0.5%, soaked for 36 hours+ temperature 40 oC which growing on media of palm oil soil+organic fertilizer (1:1)+fertilizer NPK (1g per kg media) that 83.33-86.67% and germinating speed 0.85-1.04% ctmal. There treatment also effected on seedling vigor normal vigours germination indicated by dry content weight and hypotctic vigor index. Keywords: aren, scarification, germination substrat